39.8k views
4 votes
Solve using
elimination
X- 2y = 3
3x - y = 2

User Nlogn
by
5.7k points

1 Answer

1 vote

Answer: x = 1/5 and y= -7/5

Step-by-step explanation: Let's solve your system by elimination.

Multiply the first equation by -3,and multiply the second equation by 1.

-3 (x - 2y = 3)

1 (3x - y = 2)

Becomes:

-3x + 6y = -9

3x -y = 2

Add these equations to eliminate x:

5y = -7

Then solve 5y = -7

5y/7 = -7/5

y = -7/5

Now that we‘ve found y, let’s plug it back in and solve for x.

Write down an original equation:

x - 2y = 3

Substitute -7/5 for y in x - 2y = 3:

x - 2 (-7/5) = 3

x + 14/5 = 3

x 14/5 + -14/5 = 3 + -14/5 (Add (-14)/5 to both sides)

x = 1/5

Answer:

x = 1/5 and y = -7/5

User RedGlow
by
6.0k points